CFRP - Confined reinforced concrete elements subjected to cyclic compressive loading - Ferreira, Débora (2007)
The effectiveness of discrete and continuous CFRP wrapping arrangements for reinforced concrete (RC) short column subjected to monotonic and cyclic compressive loading is assessed in this work. The experimental program is composed of four series of RC columns with discrete wrapping arrangements and one series of full wrapped RC columns. Each series is composed of a monotonic and a cyclic test. Strain gauges were installed along the height of each column to measure the strain field in the CFRP during the test. The variation of the stiffness of the unloading and reloading branches of each loading cycle was determined. A constitutive model to simulate FRP-confined RC concrete elements subjected to cyclic compressive loading was developed and implemented into a computer program based on the finite element method. This model was appraised with the data obtained from the carried out experimental program.